Continuous decision support. (1st January 2014) - Hendrix, Jeremy; Jacques, David; Weir, Jeffery D.
This paper presents extensions to the triage method for addressing continuous decision problems. These provide decision makers more tools with which to address situations where alternatives present themselves over time. The original triage method provides a criteria with which to divide these alternatives into those that should be selected, those that should be rejected, and those that should be held pending until a later decision epoch. The proposed extensions offer different criteria for accomplishing this partition. A sample problem is introduced to compare the effectiveness of the various methods and avenues for further improvements are discussed.